Assessment of surface water quality near municipal solid waste dumping facility in Bukoba, Kagera Region, Tanzania - Lema, Meserecordias W. J.; Mwegoha, William J. S. (Wiley Online LIbrary, 2024)
A research article submitted to the journal of Environmental Quality Management Volume 32, Issue 4